Reflections on Universities, Politics, and the Capitalist State: An Interdisciplinary and Intergenerational Discussion with Clyde W. Barrow - Barrow, Clyde W.; Steffen, Heather; Kamola, Isaac (ACME, 2023)
Since its publication in 1990, Clyde W. Barrow’s book, Universities and the Capitalist State: Corporate Liberalism and the Reconstruction of American Higher Education, 1894-1928, has been a touchstone text for generations of scholars studying higher education. This conversation between Barrow, Heather Steffen, and Isaac Kamola examines the book’s legacy in order to explore how the interdisciplinary study of higher education has changed over the past three decades. In doing so, they examine the space and place of academic knowledge and academic labor, offering an interdisciplinary discussion of critical praxis within the university.